Notes on ‘The Flaws in Modern Monetary Theory’ by Ricardo Carneiro - Terra, Fábio Henrique Bittes (Brazilian Keynesian Review, 2021)
This note comments the article ‘Failures of the Modern Monetary Theory’ published by Professor Ricardo Carneiro (Unicamp) in this Brazilian Keynesian Review. Agreements and disagreements with Carneiro’s paper are shown. Moreover, some points not dealt with by him, but that I understand are crucial to assess some failures of the Modern Monetary Theory, are advanced here.